IDENTIFIKASI FAKTOR-FAKTOR DALAM MENGEMBANGKAN MODEL KELEMBAGAAN INVESTASI TERPADU DI PROVINSI JAWA TIMUR - Sutjipto Ngumar; Ikhsan Budi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The purpose of this research is to dig information about factors that influence decision to invest in an area. The digging information is about service model and conducive invesment facilities in the business world.Data processing was conducted by comparing service and license between Licencing Department and Capital Investment that have not conducted One Stop Service, and respondents’ response to service and licence in those five regencies/ sities.The result of the research shows that there is a difference pattern and licencing service investment system in the regencies and cities in East Java Province. In fact, from 40 regencies and cities in East Java Province, there are five regions which form Licensing and Capital Investment Department with One Stop Service. The regencies and cities that are examined are Pasuruan Regency, Surabaya City, Gresik Regency, Sidoarjo Regency and Lamongan Regency, and there are only three regencies and cities that have not applied the policy of One Stop Service. They are Surabaya City, Gresik Regency and Lamongan Regency.Besides the efforts of increasing service in investment, investment climate is influenced by several factors, that is economic factors and non economics factor. Economic factors are export value, real income, foreign currency rate of exchange inflation, price level and credit availability. Meanwhile, non economic factors are political factor, law, security and social condition of the society. Therefore, there should be policy’s steps in order to optimize investment service in each region.